Combined loss of glyoxalase 1 and aldehyde dehydrogenase 3a1 amplifies dicarbonyl stress, impairs proteasome activity resulting in hyperglycemia and activated retinal angiogenesis - Li, Shu; Li, Hao; Bennewitz, Katrin; Poschet, Gernot; Büttner, Michael; Haußer-Siller, Ingrid; Szendrödi, Julia; Nawroth, Peter Paul; Kroll, Jens (Metabolism, 2025)
Background & aims - Any energy consumption results in the generation of highly reactive dicarbonyls and the need to prevent excessive dicarbonyls accumulation through the activity of several interdependent detoxification enzymes. Glyoxalase 1 (GLO1) knockout zebrafish showed only moderately elevated methylglyoxal (MG) levels, but increased Aldehyde Dehydrogenases (ALDH) activity and increased aldh3a1 expression. Elevated levels of 4-hydroxynonenal (4-HNE) but no MG increase were observed in ALDH3A1KO. The question of whether ALDH3A1 prevents MG formation as a compensatory mechanism in the absence of GLO1 remained unclear. - Methods - To investigate whether ALDH3A1 detoxifies MG as a compensatory mechanism in the absence of GLO1, the GLO1/ALDH3A1 double knockout (DKO) zebrafish was first generated. Various metabolites including advanced glycation end products (AGEs), as well as glucose metabolism and hyaloid vasculature were analyzed in GLO1KO, ALDH3A1KO and GLO1/ALDH3A1DKO zebrafish. - Results - In the absence of GLO1 and ALDH3A1, MG-H1 levels were increased. MG-H1 accumulation led to a severe deterioration of proteasome function, resulting in impaired glucose homeostasis and consequently amplified angiogenic activation of the hyaloid and retinal vasculature. Rescue of these pathological processes could be observed by using L-carnosine, and proteasome activator betulinic acid. - Conclusion - The present data, together with previous studies, suggest that ALDH3A1 and GLO1 are important detoxification enzymes that prevent the deleterious effects of MG-H1 accumulation on proteasome function, glucose homeostasis and vascular function.
Online verfügbar: 30. Januar 2025, Artikelversion: 11. Februar 2025
Gesehen am 12.06.2025